Future of dynamic random-access memory as main memory - Kim, Seong Keun; Popovici, Mihaela (CAMBRIDGE UNIV PRESS, 2018)
Dynamic random-access memory (DRAM) is the main memory in most current computers. The excellent scalability of DRAM has significantly contributed to the development of modern computers. However, DRAM technology now faces critical challenges associated with further scaling toward the similar to 10-nm technology node. This scaling will likely end soon because of the inherent limitations of charge-based memory. Much effort has been dedicated to delaying this. Novel cell architectures have been designed to reduce the cell area, and new materials and process technologies have been extensively investigated, especially for dielectrics and electrodes related to charge storage. In this article, the current issues, recent progress in and the future of DRAM materials, and fabrication technologies are discussed.
Keywords: ATOMIC LAYER DEPOSITION; SRTIO3 THIN-FILMS; EQUIVALENT OXIDE THICKNESS; INITIAL GROWTH-BEHAVIOR; DOPED TIO2 FILMS; ELECTRICAL-PROPERTIES; DIELECTRIC-CONSTANT; RU ELECTRODE; NM; PLASMA